Sleep Deterioration in Survivors of Community-Acquired Pediatric Septic Shock at 3-Month Follow-up - Ames, Stefanie G.; Banks, Russell K.; Reeder, Ron; Beckstead, Rylee; Groenwald, Cornelius; Meert, Kathleen L.; Zimmerman, Jerry J.; Palermo, Tonya M.; Workman, Jennifer K. (Journal of Pediatric Intensive Care, 2024)
Children who survive septic shock are at high risk of new morbidity. The objective of this study is to evaluate the occurrence and risk factors associated with new or worsening sleep disturbance, comparing baseline to 3 months following admission among children surviving septic shock. A secondary analysis of the Life After Pediatric Sepsis Evaluation prospective cohort study was performed. This study included children <18 years admitted to 12 U.S. Pediatric Intensive Care Units with community-acquired septic shock requiring vasoactive–inotropic support and invasive or noninvasive ventilation who survived discharge. The primary outcome of sleep deterioration was characterized as any increased trouble in sleeping measured by a question from the Pediatric Quality of Life Inventory (PedsQL) at baseline compared with the response at the 3-month follow-up. Child and parent variables were evaluated for association with sleep deterioration using univariable and multivariable analyses. Of the original 389 patients, 229 survived for 3 months and completed the PedsQL. The final cohort included 111 children who had available follow-up data at month 3 and did not report baseline sleep challenges. Overall, 25% (28/111) of children reported declines in sleep at 3 months. There were no patient or illness characteristics associated with sleep decline at 3 months in univariable analysis. In multivariable models controlling for age, sex, insurance type, baseline complex conditions, and immunocompromise, no measures of illness severity were associated with deterioration in sleep at 3 months. Sleep deterioration is common in survivors of community-acquired septic shock but detection may be difficult to identify without routine screening.
Keywords: septic shock; postintensive care syndrome—pediatric; sleep; quality of life